Language, culture, and society : key topics in linguistic anthropology - Jourdan, Christine; Tuite, Kevin (Studies in the social and cultural foundations of language ;, 2006)
How does language influence our perception of the world? How do children learn to use language appropriately? How far does language contribute to the formation of our personalities? In what ways does language make us human? This volume brings together a team of leading specialists to discuss these important questions.